Graphene‐Oxide‐Modified Lanthanide Nanoprobes for Tumor‐Targeted Visible/NIR‐II Luminescence Imaging. (8th November 2019) - Song, Xiaorong; Li, Shihua; Guo, Hanhan; You, Wenwu; Shang, Xiaoying; Li, Renfu; Tu, Datao; Zheng, Wei; Chen, Zhuo; Yang, Huanghao; Chen, Xueyuan
Abstract: The synthesis of hydrophilic lanthanide‐doped nanocrystals (Ln 3+ ‐NCs) with molecular recognition ability for bioimaging currently remains a challenge. Herein, we present an effective strategy to circumvent this bottleneck by encapsulating Ln 3+ ‐NCs in graphene oxide (NCs@GO). Monodisperse NCs@GO was prepared by optimizing GO size and core–shell structure of NaYF4 :Yb, Er@NaYF4, thus combining the intense visible/near‐infrared II (NIR‐II) luminescence of NCs and the unique surface properties and biomedical functions of GO. Such nanostructures not only feature broad solvent dispersibility, efficient cell uptake, and excellent biocompatibility but also enable further modifications with various agents such as DNA, proteins, or nanoparticles without tedious procedures. Moreover, we demonstrate in proof‐of‐concept experiments that NCs@GO can realize simultaneous intracellular tracking and microRNA‐21 visualization, as well as highly sensitive in vivo tumor‐targeted NIR‐II imaging at 1525 nm. Abstract : Nanosonde to GO : Eine Graphenoxid (GO)‐modifizierte lumineszierende Lanthanoid‐Nanosonde mit exzellenter Dispersibilität und Biokompatibilität ermöglicht einfache Oberflächenmodifikationen mit DNA, Protein oder Nanopartikeln. Die Nanosonde lässt sich für simultane intrazelluläre Verfolgung und microRNA‐21‐Visualisierung sowie die hochempfindliche NIR‐II‐Bildgebung von Maustumoren maßschneidern.